Cochlin-tomoprotein: A novel perilymph-specific protein and a potential marker for the diagnosis of perilymphatic fistula - Tetsuo Ikezono (2018)
Background: Perilymphatic fistula (PLF) is an abnormal connection between the inner and middle ear. A procedure for obtaining definite proof of a PLF remains elusive, and methods of diagnosis remain controversial. To date, there is no clinically relevant biochemical marker for perilymph leakage. Using proteomic analysis of inner ear proteins, we have previously found unique properties of cochlin, encoded by the COCH gene. We detected 3 cochlin isoforms (p63s, p44s and p40s) in the inner ear tissue and a short 16-kDa isoform of cochlin-tomoprotein (CTP) in the perilymph. Since cochlin was found to be highly specific to the inner ear, we speculated that CTP might also be specific to the perilymph. The aim of this study was to determine whether CTP, a novel perilymph-specific protein, could be used as a marker for the diagnosis of PLF. Methods: By Western blotting, we investigated the specificity of CTP expression in a range of body fluids that included perilymph, serum, saliva and cerebrospinal fluid. To elucidate the detection limit of CTP, serially diluted recombinant human (rh)CTP as well as human perilymph was tested. Results: CTP was selectively expressed in all 20 perilymph samples tested, but not in 77 samples of the other body fluids. The detection limit of rhCTP was 0.27 ng or 0.022 μl of perilymph per well on Western blot analysis. Conclusion: The results strongly suggest that CTP can be a specific marker of perilymph leakage. Moreover, CTP has the potential to be a biochemical marker that allows a definitive diagnosis of the etiology of PLF-related hearing loss and vestibular disorders. Copyright © 2009 S. Karger AG.